Indoor wood-burning from stoves and fireplaces and incident lung cancer among Sister Study participants - Suril S. Mehta; M. Elizabeth Hodgson; Ruth M. Lunn; Claire E. Ashley; Whitney D. Arroyave; Dale P. Sandler; Alexandra J. White (Environment International, 2023)
Background and aim: Epidemiological studies conducted mostly in low- and middle-income countries have found a positive association between household combustion of wood and lung cancer. However, most studies have been retrospective, and few have been conducted in the United States where indoor wood-burning usage patterns differ. We examined the association of exposure to indoor wood smoke from fireplaces and stoves with incident lung cancer in a U.S.-wide cohort of women. Methods: We included 50,226 women without prior lung cancer participating in the U.S.-based prospective Sister Study. At enrollment (2003–2009), women reported frequency of use of wood-burning stoves and/or fireplaces in their longest-lived adult residence. Cox regression was used to estimate adjusted hazard ratios (HRadj) and 95 % confidence intervals (CI) for the association between indoor wood-burning fireplace/stove use and incident lung cancer. Lung cancer was self-reported and confirmed with medical records. Results: During an average 11.3 years of follow-up, 347 medically confirmed lung cancer cases accrued. Overall, 62.3 % of the study population reported the presence of an indoor wood-burning fireplace/stove at their longest-lived adult residence and 20.6 % reported annual usage of ≥30 days/year. Compared to those without a wood-burning fireplace/stove, women who used their wood-burning fireplace/stove ≥30 days/year had an elevated rate of lung cancer (HRadj = 1.68; 95 % CI = 1.27, 2.20). In never smokers, positive associations were seen for use 1–29 days/year (HRadj = 1.64; 95 % CI = 0.87, 3.10) and ≥30 days/year (HRadj = 1.99; 95 % CI = 1.02, 3.89). Associations were also elevated across all income groups, in Northeastern, Western or Midwestern U.S. regions, and among those who lived in urban or rural/small town settings. Conclusions: Our prospective analysis of a cohort of U.S. women found that increasing frequency of wood-burning indoor fireplace/stove usage was associated with incident lung cancer, even among never smokers.